Historiographical Review of the Problem "Woman of the USSR in the Great Patriotic War – Hero or Victim?" - SAKTAGANOVA, Zauresh; SAGATOVA, Assem; NURLIGENOVA, Zauresh (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The researchers often addressed various aspects of the Great Patriotic War, but the problem of "women and war" has rarely attracted the attention of researchers. Depending on the theoretic-methodological and conceptual approaches, the specifics of the sources involved, the range and depth of the problems raised among the whole set of available publications, the authors of the article highlighted three main types in historiography: Soviet, modern Kazakhstan and foreign (Russian and Western) historiography. The main trends that characterize each of these groups have been identified. It is concluded that in Soviet and Kazakhstan historiography many layers of problems were out of the research field: women never became objects of study.RESUMEN Los investigadores a menudo abordaron varios aspectos de la Gran Guerra Patria, pero el problema de "mujeres y guerra" rara vez ha atraído la atención de los investigadores. Dependiendo de los enfoques teórico-metodológicos y conceptuales, los detalles de las fuentes involucradas, el alcance y la profundidad de los problemas planteados, entre todo el conjunto de publicaciones disponibles, los autores del artículo destacaron tres tipos principales en historiografía: la Unión Soviética, la moderna Kazajstán e historiografía extranjera (rusa y occidental). Se han identificado las principales tendencias que caracterizan a cada uno de estos grupos. Se concluye que en la historiografía soviética y de Kazajstán mucho de los problemas estaban fuera del campo de investigación: las mujeres nunca se convirtieron en objeto de estudio exhaustivo.